Strengthening cooperation and security in South Asia post 9/11 - Sobhan, Farooq; Bangladesh Enterprise Institute (Dhaka : University Press Ltd., 2004)
Contributed papers presented at two regional conferences organized by Bangladesh Enterprise Institute in July 1-2, and September 23-24, 2003 at Dhaka, Bangladesh.
Includes bibliographical references.
Keywords: National security -- South Asia -- Congresses; National security -- South Asia -- International cooperation -- Congresses; September 11 Terrorist Attacks, 2001 -- Influence -- Congresses; South Asian cooperation -- Congresses